Molecular Characteristics and Distribution of Adult Human Corneal Immune Cell Types - Li, Yanxiu; Li, Haibo; Xia, Xiaobo (Frontiers in Immunology, 2022)
Background: The limbus is placed at a 2-mm-wide area between the bulbar conjunctiva and the cornea and has been suggested to be the niche of corneal epithelial stem cells and immune cells. Like skin and intestines, the cornea is also an important mucosal surface and immune cells on the cornea play critical roles in immune surveillance to ensure barrier surface homeostasis and protection from various environmental damages and infection. Single-cell RNA sequencing (scRNA-seq) analysis of PTPRC positive hematopoietic cells from the corneal limbus could provide a single cell atlas of all the immune cell subsets. Methods: We performed a single cell transcriptomic profiling of sorting purified 804 PTPRC positive hematopoietic cells from corneas of 3 healthy donors. Results: Our analysis identified a primary transcriptomic pattern for multiple immune cell subtypes such as naïve T cells, antiviral effector CD8+ T cells and innate immune cells like IDO1+ mature regulatory dendritic cells (mregDC), macrophages, monocytes and basophils in the human corneal limbus. Conclusion: Overall, single cell transcriptomic analysis of limbal immune cells suggest the possible contribution of these cells on adaptive and innate immune response of the human cornea.